Extranodal natural killer/T-cell lymphoma invading a patient’s heart: A rare case report and literature review - Xiang, Yifei; Lin, Xueqin; Cai, Xiaoling; Qu, Shuang; Lin, Kai-Yang (Frontiers in Oncology, 2022)
Extranodal NK/T-cell lymphoma (ENKTL) is a rare but aggressive subtype of non-Hodgkin lymphoma, which is derived from NK cells or T cells. There are very few cases of ENKTL invading the heart. Only 12 cases of ENKTL invading the heart have been reported in the English literature. Due to the rarity of this lymphoma, an effective therapeutic strategy has not been defined. Here, we present a case of a 51-year-old Chinese male with extranodal NK/T-cell lymphoma invading the heart and review the literature. The patient received a chemotherapy regimen of PD1 monoclonal antibody (Sintilimab) in combination with first-line P-Gemox. The patient survived for 2 months after diagnosis.